2019
DOI: 10.1021/acs.cgd.9b00041
|View full text |Cite
|
Sign up to set email alerts
|

Average Structure, Local Structure, Photoluminescence, and NLO Properties of Scheelite Type NaCe(WO4)2

Abstract: Phase pure nanoparticles of NaCe(WO 4 ) 2 green phosphor were synthesized via a template-free solvothermal method using water (NaCeW-a) and ethylene glycol (NaCeWb) as reaction solvents. Rietveld refinements using powder neutron diffraction (NPD) data confirms that both NaCeW-a and NaCeWb crystallize in the Scheelite-like tetragonal I4 1 /a space group. However, local structure analysis using total scattering atomic pair distribution function (PDF) refinements in a shorter 'r' range (1.5 to 10 Å) established t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Likewise, local deviations from the average symmetry play a crucial role in determining the materials’ ability to function as frequency-doubling crystals. Recently, Munirathnappa and co-workers demonstrated that the combined use of Rietveld and PDF analysis serves to rationalize second harmonic generation in NaCe­(WO 4 ) 2 . Similar to our findings, these authors reported that Na/Ce–O 8 dodecahedra appear locally distorted and that PDF analysis is able to capture these short-range bond distance distortions (Δ (Na/Ce)O 8 : 14 × 10 –3 –25 × 10 –3 ) whereas Rietveld analysis is not (Δ (Na/Ce)O 8 : 3 × 10 –3 –9 × 10 –3 ).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Likewise, local deviations from the average symmetry play a crucial role in determining the materials’ ability to function as frequency-doubling crystals. Recently, Munirathnappa and co-workers demonstrated that the combined use of Rietveld and PDF analysis serves to rationalize second harmonic generation in NaCe­(WO 4 ) 2 . Similar to our findings, these authors reported that Na/Ce–O 8 dodecahedra appear locally distorted and that PDF analysis is able to capture these short-range bond distance distortions (Δ (Na/Ce)O 8 : 14 × 10 –3 –25 × 10 –3 ) whereas Rietveld analysis is not (Δ (Na/Ce)O 8 : 3 × 10 –3 –9 × 10 –3 ).…”
Section: Resultssupporting
confidence: 88%
“…Refinements were performed in the 1.4−25°2θ range. The following parameters were refined: (1) scale factor; (2) background, which was modeled using a shifted Chebyschev polynomial function; (3) peak shape, which was modeled using a Thompson−Cox−Hastings pseudo-Voigt function; 16 constrained by the site symmetry (U 11 and U 33 for Na, RE, and M; U 11 , U 22 , U 33 , U 12 , U 13 , and U 23 for O). R wp residuals and difference curves were employed to assess the quality of the refined structural models.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations